2012
DOI: 10.1089/neu.2011.2225
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Principal Strain Correlates with Spinal Cord Tissue Damage in Contusion and Dislocation Injuries in the Rat Cervical Spine

Abstract: The heterogeneity of the primary mechanical mechanism of spinal cord injury (SCI) is not currently used to tailor treatment strategies because the effects of these distinct patterns of acute mechanical damage on long-term neuropathology have not been fully investigated. A computational model of SCI enables the dynamic analysis of mechanical forces and deformations within the spinal cord tissue that would otherwise not be visible from histological tissue sections. We created a dynamic, three-dimensional finite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…Interestingly, for a wide variety of spinal cord injury models (i.e. compression, dislocation, distraction, and hyperextension — Choo et al, 2007, 2008; Clarke et al, 2008; Lam et al, 2014; Li and Dai, 2009; Russell et al, 2012; Seifert et al, 2011), axonal injury has been shown to be most predominant in the ventral white matter. Such injury is not, however, necessarily limited to neurofilament compaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, for a wide variety of spinal cord injury models (i.e. compression, dislocation, distraction, and hyperextension — Choo et al, 2007, 2008; Clarke et al, 2008; Lam et al, 2014; Li and Dai, 2009; Russell et al, 2012; Seifert et al, 2011), axonal injury has been shown to be most predominant in the ventral white matter. Such injury is not, however, necessarily limited to neurofilament compaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of investigators have developed finite element models of the spinal cord (Lam et al, 2014; Li and Dai, 2009; Maikos et al, 2008; Russell et al, 2012; Sparrey et al, 2009) to evaluate biomechanical forces during spinal injuries. Interestingly, these models generally predict significant damage to the ventral white matter, even without necessarily positing compression of the spinal cord against the inner surface of the vertebral column.…”
Section: Discussionmentioning
confidence: 99%
“…35 In this sense, it would be possible to study the response of the SPCL scaffolds to mechanical stresses usually found in the human body. Additionally, the spine model may be combined with an SCI mathematical model, as the one described by Russell and colleagues, 36 in order to further understand the neuroprotective effect of SPCL stabilization in an SCI situation.…”
Section: Discussionmentioning
confidence: 99%
“…The primary injury is considered to be disruption of neural tissue as the immediate result of the blunt, non-penetrating mechanical forces applied at high velocity to the spinal cord as the surrounding bony/ligamentous spinal column fails. Primary mechanical trauma exerts distraction, compression, and shear forces on the spinal cord (4, 5), and can cause damage not only to the central nervous system (CNS) but also the peripheral nervous system (6). Vascular, cellular and axonal damage occurs almost instantaneously and continues to spread from the injury epicenter both radially and axially.…”
Section: Introductionmentioning
confidence: 99%